Perencanaan Inovasi Kewirausahaan bagi Majlis Taklim: Membangun Dakwah Mandiri dan Berkelanjutan - Istianah Istianah; Cecep Castrawijaya (CV. ITTC INDONESIA, 2025)
Majlis taklim plays a vital role in community religious education, yet often faces challenges such as limited funding, reliance on donors, and weak modern management models. These conditions require innovative entrepreneurial planning to strengthen the institution’s economic base and ensure sustainable da’wah. This study employs a qualitative method using literature review and descriptive analysis on Islamic entrepreneurship, da’wah management, and case studies of majlis taklim with sharia-based enterprises. The findings reveal that entrepreneurial innovation planning, supported by SWOT analysis, enables majlis taklim to design adaptive strategic visions. Innovative practices such as halal product businesses, sharia cooperatives, and digital platforms strengthen the independence of da’wah activities. Although constrained by limited human resources and low entrepreneurial literacy, development opportunities remain open through managerial capacity building and collaboration. Thus, entrepreneurial innovation serves as an effective strategy for majlis taklim to achieve independent and sustainable da’wah.